In Vitro Antibacterial Activity and Phytochemical Screening of Galoba (Hornstedtia alliaceae) Seeds Extract - Melfan El Shaday Sule; Eka Astuty; Ritha Tahitu (Bioactivities, 2023)
Hornstedtia alliacea has been traditionally used by indigenous people for a variety of medicinal purposes. This study aimed to determine the antibacterial activity of ethanol extracts of Galoba seeds (Hornstedtia alliacea) against standard bacterial cultures of Staphylococcus aureus (ATCC-29213) and Escherichia coli (FNCC-6183) using Kirby-Bauer disk diffusion method. The phytochemical tests were carried out to determine the presence of active substances which are antibacterial in the results of the extraction. The color intensity or the precipitate formation was used as analytical response to these tests. The major phytochemical constituents identified in galoba seeds ethanol extracts were tannins, flavonoids, saponins, quinones, and steroids. The antibacterial assay showed that galoba seed extract inhibited the growth of S. aureus and E. coli. The diameter of the inhibition zone increased as the extract concentration increased. The largest inhibition zone for S. aureus was at a concentration of 100% with a diameter of 20.93 mm and the largest inhibition zone for E. coli was at a concentration of 100% with a diameter of 18.05 mm. The results of this study indicated that the plant contains some major bioactive compounds that inhibit the growth of microorganisms, thereby showing great potency as an effective source of drugs. The phytochemical analysis also reveals that the plant contains similar constituents useful for medicinal purposes.